Crying laughing - Rubin, Lance, 1981- (New York : Alfred A. Knopf, 2019)
"Winnie Friedman has been waiting for the world to catch on to what she already knows: she's hilarious. It might be a long wait, though. After bombing a stand-up set at her own bat mitzvah, Winnie has kept her jokes to herself. Well, to herself and her dad, a former comedian and her inspiration. Then, on the second day of tenth grade, the funniest guy in school actually laughs at a comment she makes in the lunch line and asks her to join the improv troupe. Maybe he's even...flirting? Just when Winnie's ready to say yes to comedy again, her father reveals that he's been diagnosed with ALS. That is...not funny. Her dad's still making jokes, though, which feels like a good thing. And Winnie's prepared to be his straight man if that's what he wants. But is it what he needs? Caught up in a spiral of epically bad dates, bad news, and bad performances, Winnie's struggling to see the humor in it all. But finding a way to laugh is exactly what will see her through"--From the publisher's web site.
"So funny it hurts"--Cover.
Junior Library Guild
Ages 14-17.
Grades 9-12.
HL740
A Junior Library Guild selection
Keywords: Amyotrophic lateral sclerosis -- Juvenile fiction; Comedians -- Juvenile fiction; Fathers and daughters -- Juvenile fiction; Amyotrophic lateral sclerosis -- Fiction; Comedians -- Fiction; Fathers and daughters -- Fiction; Amyotrophic lateral sclerosis -- Fiction; Comedians -- Fiction; Father-daughter relationship -- Fiction